Digital health app development standards: a systematic review protocol. Issue 8 (17th August 2018) - Van Velthoven, Michelle Helena; Smith, James; Wells, Glenn; Brindley, David
Abstract : Introduction: There is currently a lack of clear and accepted standards for the development (planning, requirement analysis and research, design and application testing) of apps for medical and healthcare use which poses different risks to developers, providers, patients and the public. The aim of this work is to provide an overview of the current standards, frameworks, best practices and guidelines for the development of digital health apps. This review is a critical 'stepping stone' for further work on producing appropriate standards that can help mitigate risks (eg, clinical, privacy and economic risks). Methods and analysis: A systematic review identifying criteria from applicable standards, guidelines, frameworks and best practices for the development of health apps. We will draw from standards for software for medical devices, clinical information systems and medicine because of their relatedness and hope to apply lessons learnt to apps. We will exclude other types of publications, and those published in languages other than English. We will search websites of relevant regulatory and professional organisations. For health apps, we will also search electronic research databases (eg, MEDLINE, Embase, SCOPUS, ProQuest Technology Collection and Engineering Index) because relevant publications may not be found on other websites. We will hand-search reference lists of included publications. The review will focus on international, USA, European and UK standards because these are the markets of primary interest to the majority of app developers currently. We will provide a narrative overview of findings and tabular summaries of extracted data. Also, we will examine the relationship between different standards and compare USA and European Union standards. Ethics and dissemination: No ethics approval is required. The review will be disseminated through peer-reviewed publications, conference presentations and inform efforts that aim to improve the quality of health apps through existing links with relevant organisations.